From Leaf to Extract: A Cost-Benefit and Input-Output Assessment of Kratom Down streaming in Indonesia - Akbar Nusantara, Sandy; Aswin Rahadi, Raden (Journal Research of Social Science, Economics, and Management, 2026)
Indonesia is one of the world’s largest producers of kratom (Mitragyna speciosa), yet it captures only a small share of the value generated along the global kratom value chain. The enactment of Permendag 20/2024 and 21/2024 in October 2024, which prohibits raw kratom leaf exports and mandates processed-form exports, has created both an obligation and an opportunity to move downstream into high-purity extraction. This study assesses the financial feasibility and macroeconomic impact of producing fifty-percent mitragynine extract at a commercial scale of one hundred kilograms per month, using the case of PT MIT as the unit of analysis. An integrated framework combining a firm-level Cost-Benefit Analysis with an Input-Output Analysis is applied, grounded in validated pilot operational data and the 2020 Indonesian Input-Output Table. Three scenarios distinguished by capacity utilization of seventy-five, eighty-five, and ninety-three percent are evaluated at a fifteen-percent discount rate. The financial results indicate strong viability: the base case yields a net present value of Rp 11.80 billion, an internal rate of return of 37.59 percent, a profitability index of 2.31, and a discounted payback of 4.88 years. The macroeconomic results show that the pharmaceutical sector to which kratom extraction is mapped functions as a strong demand-pull sector, generating total economy-wide output of Rp 48.37 billion, supporting around ninety-three jobs, and contributing foreign exchange of USD 1.53 million per year. The study demonstrates that domestic down streaming aligns private profitability with national economic benefit.